2015
DOI: 10.5152/tao.2015.985
|View full text |Cite
|
Sign up to set email alerts
|

Tularemia: A Rare Cause of Neck Mass

Abstract: Objective: Tularemia is a bacterial zoonosis caused by Francisella tularensis. In this study, we aimed to retrospectively evaluate the documents of patients who had a diagnosis of tularemia in our hospital and discuss this condition with a literature review. Methods:Twenty-five patients who had a diagnosis of tularemia between 2010 and 2013 were included in the study. The patients were assessed with respect to their demographic data; presenting complaints; leukocyte, sedimentation, and C-reactive protein (CRP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…Fourth, blood inflammatory markers, in particular C-reactive protein (CRP), were mostly low ( Supplementary Figure 4D ). This finding differs from what has been reported in adult patients with oropharyngeal disease [ 56 ]. Other investigators found that CRP values in pulmonary disease were higher than in ulceroglandular disease in adults and peaked in the first week of illness [ 57 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Fourth, blood inflammatory markers, in particular C-reactive protein (CRP), were mostly low ( Supplementary Figure 4D ). This finding differs from what has been reported in adult patients with oropharyngeal disease [ 56 ]. Other investigators found that CRP values in pulmonary disease were higher than in ulceroglandular disease in adults and peaked in the first week of illness [ 57 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Tularemia has generally assumed greater importance in Turkey in recent years because of outbreaks deriving from water sources [20,21]. Aktas et al reported an outbreak of 55 cases of oropharyngeal tularemia detected in 2013 and derived from drinking water [13].…”
Section: Discussionmentioning
confidence: 99%
“…It is also effective in children at 15 mg/kg/day over the same period. The therapeutic period may sometimes exceed two weeks in patients with slow clinical improvement [21,38].…”
Section: Discussionmentioning
confidence: 99%